Membangun Daya Tarik Jasa dan Reputasi Merek Melalui Kualitas Layanan dan Aliansi Pasar Pada Perusahaan EMKL - Susilowati, Luky (Jurnal Riset Ekonomi dan Bisnis, 2009)
Marketer common wishing that satisfied customer can keeping. This not easy duty remember the change can be happened anytime, good of change of itself and also appetite psychological aspect and also environmental condition change. In emulation environment which progressively tighten with entry of product innovative to marketing in one side and saturated market condition for the product of certain on the other side, duty manage the loyalty of customer become the not an easy challenge managerial. One of theme which still be limited in number research literature is topic studying use of marketing alliance, where marketing alliance represent the lateral relation at enchain the same added value and form of the symbiosis in mutual profit marketing (symbiotic marketing). Others alliance even also instruct at development a inwrought concept is make-up of cognate element of consumer to brand reputation from product marketing with. This research aim to know the Influence of Marketing Alliance of to Service Quality and also its impact to Brand Reputation and Services Attraction at one of EMKL in Surabaya.Primary data used in this research, purposive sampling has been taken to identify the sample, there was the customer’s of EMKL. Data analyzed by SEM (Structural Equation Modeling) approach through AMOS program.The result of this research show that, Marketing Alliance have positive  influence to Service Quality,  Service Quality do not have an effect on to Brand Reputation, and Service Quality have positive influence to Services Attraction.Keywords : Marketing Alliance, Service Quality, Brand Reputation, Services Attraction